PENDEKATAN PENDIDIKAN AGAMA ISLAM TERHADAP PERILAKU MENYIMPANG SISWA DI ERA DIGITAL: STUDI KONTEKSTUAL DI PONDOK TAHFIDZ AL-FATAH KURIPAN LOR: Islamic Religious Education Approach Towards Deviant Behavior Of Students In The Digital Era: A Contextual Study At The Al-Fatah Tahfidz Boarding School, Kuripan Lor - Widiyanto, Urip; Fadli, Failasuf (STAI Ma'had Aly Al-Hikam Malang, 2025)
The digital era has a significant impact on the behavioral development of adolescents, including students in Islamic educational institutions. Unlimited access to information technology often triggers deviant behavior such as gadget addiction, a decline in manners, and the erosion of Islamic values. This study aims to examine relevant Islamic Religious Education approaches to addressing student deviant behavior in the digital era, with a contextual focus on the Al-Fatah Islamic Boarding School in Kuripan Lor. Using a library study method, data was obtained from various relevant scientific literature. The study results indicate that exemplary behavior, habituation of pious deeds, and a psychological-religious approach are highly effective in fostering student character in the digital era. The implementation of these approaches at Al-Fatah Islamic Boarding School has proven effective in strengthening students' spiritual values and minimizing the negative influence of digital media. This study supports the important role of Islamic Religious Education teachers as spiritual guides and moral role models in facing the challenges of the times.